Katherine Parr, Translation, and the Dissemination of Erasmus’s Views on War and Peace - White, Micheline (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2020)
This article offers new evidence of Katherine Parr’s activities as a translator by demonstrating that she translated two prayers from Erasmus’s Precationes aliquot novæ in 1544. The first, “A Prayer for Men to Say Entering into Battle,” appeared in all the editions of Parr’s Psalms or Prayers; the second, “A Prayer for Forgiveness of Sins,” was included only in sextodecimo editions. These newly recovered translations have important implications for our understanding of Parr’s involvement in Henry VIII’s war effort and for the history of the dissemination of Erasmus’s ideas in England. This study argues that Parr’s translations provide new evidence that she collaborated with Thomas Cranmer and Henry VIII in producing wartime propaganda but also that Parr reframed, edited, and distorted Erasmus’s prayers to promote Henry’s wartime needs. This data has additional repercussions because Parr was also the sponsor of the translation of Erasmus’s Paraphrases on the New Testament, a text that exhorted Henry and other princes to avoid war and embrace peace. Parr, then, was at the heart of two translation projects that were fundamentally at odds with one another, and her translations can be described as important interventions into Erasmus’s legacy in England.